The Agents Of Environmental Education Through Women's School In Karanganyar, Tempurejo Village, Tempurejo Sub-District, Jember Regency - Agustina Dewi Setyari (Pancaran Pendidikan, 2018)
Environmental education is badly needed today because a lot of developments often ignore the environment care. Understanding of caring for the environment cannot be built instantly but it must begin early. The role of women in conducting environmental education is very important. In reviewing eco-feminism, this role is certainly inseparable from gender role attached to women as guards of life and the environment. It can be seen from the term of mother and the name of the goddess of fertility which is always symbolized by woman. This situation has made many women learn about the environment. Consequently, this makes women have education and knowledge that are quite related to the environment. Through women's school, the role of women as guards of environment is expected to be more optimal. Through this women's school, women are expected to be able to form environmental literacy groups which can later become the agents of environmental education for the community.